IPA3 non-specifically enhances phosphorylation of several proteins in human platelets. (July 2015) - Badolia, Rachit; Manne, Bhanu Kanth; Dangelmaier, Carol; Kunapuli, Satya P.
Abstract PAK (p21-Activation kinase), a serine-threonine protein kinase contains an autoinhibitory domain that suppresses the catalytic activity of its kinase domain. This autoregulatory domain found within PAK kinase provides a unique target for chemical inhibitors. IPA3, a small molecule allosteric inhibitor of PAK activation, binds covalently to the PAK regulatory domain and prevents binding to its upstream activators. IPA3 has been used in various cells including platelets to evaluate the role of PAK in signaling. In a recent study, PAK functions in platelet aggregation and lamellipodia formation were evaluated using IPA3 as the PAK inhibitor. Herein, we investigated the specificity and selectivity of IPA3 as a PAK inhibitor in the human platelets. Stimulation of platelets pretreated with IPA3 using a PAR-4 or GPV1 agonist resulted in a concentration-dependent inhibition of aggregation, as was suggested by earlier studies. Interestingly, we found that incubation of washed human platelets with IPA3 lead to a non-specific increase in phosphorylation of several proteins in absence of any agonist. However, this phosphorylation is not sufficient for aggregation of platelets by IPA3. In summary, we demonstrate that IPA3 by itself can phosphorylate several proteins in human platelets and thus its use is not an appropriate strategy for investigating PAK function in platelets.